Design of Educational Games of The introduction of Nutritious Food For Kids - Sri Desi Mulyaningsih; Brenda Chandrawati; Hendra Prasetya (SISFORMA, 2015)
Keeping the food supply is done continuously since we were a child. But in fact, children’s awareness of having balanced – nutrition of dietary habit is still limited.Then the idea to develop educational game to introduce nutritious food to children came. The results of the study generates that 29 out of 30 respondents had never played an educational game with the material related to nutritious food. And all the respondents said that they wereall interested in the idea of developing educational game to introduce nutritious food to children